FORMULATION DEVELOPMENT AND IN VITRO PENETRATION TEST OF ETHOSOME OF CHROMOLAENA ODORATA LEAVES EXTRACT - RAHMI, SOFIA; REVENY, JULIA; ARIANTO, ANAYANTI; SITORUS, PANAL (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aimed to develop and assess ethosome preparation using extracts derived from the leaves of Chromolaena odorata. Methods: The study started by obtaining Chromolaena odorata leaf extracts. Furthermore, Ethosome formulations were produced using a thermal technique. Ethosome variants were created, each with distinct compositions: Formulation F1, containing 10 ml of ethanol without the extract; Formulation F2, consisting of 0.5 grams of the extract mixed with 10 ml of ethanol; Formulation F3, combining 1 gram of the extract with 20 ml of ethanol; and Formulation F4, incorporating 1.5 grams of the extract with 30 ml of ethanol. The ethosomal systems were thoroughly characterized using various analytical techniques, such as organoleptic analysis, quantification of particle dimensions, zeta potential evaluation, pH metric analysis, transmission electron microscopy (TEM) imaging, and in vitro permeability assessment using the Franz Diffusion Cell apparatus. Results: The findings indicated that the optimized F4 formulation showed 161.2±32.0 nm particle size measurement and a+34.33±0.58 mV zeta potential. All formula possess a pH range of 4.5-6.5, within which the skin can acclimate to preparations. It is evident from all formulations that the pH decreased after the addition of the extract at an acidic pH of 4.11. Following the 12-week storage period, the pH of all treatments exhibited a modest reduction; however, it remained within the acceptable range for skin pH. Furthermore, the F4 formula also had a higher level of penetration activity. Conclusion: The optimized ethosomal formulations of Chromolaena odorata have promising applications in enhancing the permeability and efficacy of plant-derived therapeutic agents.